2006
DOI: 10.1002/jcp.20584
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix deposition by fibroblasts is necessary to promote capillary‐like tube formation in vitro

Abstract: The contribution of the cellular and fibrillar microenvironment to angiogenesis still remains unclear. Our purpose was to evaluate the effect of the extracellular matrix deposited by fibroblasts on the capacity of human endothelial cells to form capillaries in vitro. We have drastically decreased the amount of extracellular matrix surrounding fibroblasts in our model of endothelialized-reconstructed connective tissue (ERCT) by culturing it without ascorbate. Under these conditions, the number of capillary-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
99
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 25 publications
2
99
0
1
Order By: Relevance
“…Coculturing with an additional cell type to serve as mural cells and inclusion of ECM are necessary to maintain and mature the networks (5-11). The ability to precisely control in vitro experimental conditions directly led to identifying the mechanisms of many fundamental aspects of this process over the past several decades (5)(6)(7)(10)(11)(12)(13)(14). Several groups have recently shown that microvascular structures that are preformed in vitro by using endothelial and smooth muscle progenitor cells can anastomose with the host vasculature when implanted in a nude mouse model (15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Coculturing with an additional cell type to serve as mural cells and inclusion of ECM are necessary to maintain and mature the networks (5-11). The ability to precisely control in vitro experimental conditions directly led to identifying the mechanisms of many fundamental aspects of this process over the past several decades (5)(6)(7)(10)(11)(12)(13)(14). Several groups have recently shown that microvascular structures that are preformed in vitro by using endothelial and smooth muscle progenitor cells can anastomose with the host vasculature when implanted in a nude mouse model (15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…5, right panel). The vascular conduits in the implants of hypoxic mice were also immature, poor in collagen, thin-walled, and apparently friable, often ruptured, and resembled cells seen in ascorbic acid depletion when collagen deposition is impaired (6).…”
Section: Resultsmentioning
confidence: 96%
“…24 Understanding this process remains a challenge, since fibroblasts have the capacity to alter the mechanical extracellular microenvironment, thereby regulating vascularization processes. 25 Fibroblast-derived proteins, including growth factors and matrix proteins, have been shown to modulate EC sprouting and the expansion of capillary-like networks in vitro, [26][27][28] contributing to the role of fibroblasts as periendothelial cells in vivo. 29 Thus, the hypothesis underlying herein is that, when cocultured with OECs or mature ECs, different types of fibroblasts will exert distinct influences in the assembly of capillary-like structures.…”
mentioning
confidence: 99%